Musculoskeletal pain and perceived stress by teachers during the COVID-19 pandemic (Research, Society and Development, 2021)
Objective: To analyze the presence of musculoskeletal pain and perceived stress in university professors in times of COVID-19 pandemic. Methods: Cross-sectional study of quantitative analysis carried out with the faculty of a higher education institution between the months of October, December 2020. Data collection was performed using a sociodemographic and professional questionnaire, from the Nordic Musculoskeletal Questionnaire (QNSO) and the Stress Perception Scale-10 (PSS-10). Results: Most of the 51 participants were women (64.7%); aged between 31 and 49 years (59.6%); married (66.7%) and with children (58.8%). They had a specialization and a master's degree (41.2%); two jobs (62.7%); total workload of more than 40 hours per week (41.2%); with monthly income between four and six minimum wages (35.3%); and with working time in the institution of up to five years (58.8%). The teachers' main musculoskeletal complaint was in the back region, including the trigger for seeking health care. Only the problems related to the elbows did not prevent them from carrying out their normal activities in the last year. Conclusion: The period of remote activity indicates a perception of stress above the average in 45.1% of the participants, being directly related to the existence of musculoskeletal disorders in the neck and shoulders in the last 12 months.